Pengaruh Kecerdasan Emosional Terhadap Perilaku Prososial Siswa Boarding School MTS Negeri 1 Pati - Zakya Ma’rifatus Salwa; Ambarwati (Universitas Pakuan, 2026)
THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON PROPOSAL BEHAVIOR OF BOARDING SCHOOL STUDENTS AT MTs NEGERI 1 PATI This study aims to describe students’ emotional intelligence and prosocial behavior and to examine the influence of emotional intelligence on prosocial behavior among boarding school students at MTs Negeri 1 Pati. The study is grounded in the boarding school context, where students are required to engage in continuous social interaction throughout the day. In such an environment, the ability to recognize, understand, and regulate emotions becomes an essential foundation for developing positive social behavior. This research employed a quantitative approach involving 54 students from grades VII and VIII. Data were collected using psychological scales and analyzed through descriptive statistics and simple linear regression. The findings indicate that students’ emotional intelligence was in the good category, with an average score of 49.68. Self-motivation appeared as the strongest indicator, while emotional regulation remained an aspect that needed further improvement. Students’ prosocial behavior was also categorized as good, with an average score of 50.41, particularly reflected in their obedience to religious and social norms. The hypothesis test revealed that emotional intelligence had a positive and significant effect on prosocial behavior, contributing 44% to its development. Therefore, higher emotional intelligence is associated with stronger prosocial behavior among students in the boarding school environment.